CHEMICAL COMPOSITION AND FUNCTIONAL PROPERTIES OF THE AFRICAN LOCUST BEAN (PARKIA BIGLOBOSA) SEEDS (Biological Sciences - PJSIR, 2002)
The proximate and nutritionally valuable  mineral  compositions were  determined  in  raw, cooked  and  fermented  Afri can locust bean seeds (ALBS). The functional  properties were also evaluated  in  the fermented  sample. Results showed that fermentation improved protein , ash and calcium quantitatively in over cooked sample while fat, carbohyd rate, magnesium, sodium, phosphorus, zinc and iron values were more concentrated in the cooked sample. The functional property results showed that fermented ALBS was poor in most functional properties except  i n  water  absorption capacity. Protein solubility was high in the acid and alkaline media while the isoelectric point was 7.0 showing that fermented  ALBS would  be  useful  in food  formulations involving  both  low and  high  pH.